Prosedur Pengelolaan Keuangan pada Dinas Pemuda, Olahraga, Kebudayaan dan Pariwisata Kabupaten Kapuas - Kusumawardani, Vivi Pancasari (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
This study aims to determine the procedure for managing financial statements at the Kapuas District Office of Youth, Sports, Culture and Tourism.The data used in this study are documentary data, while the data sources used are secondary data with data collection technique in the form of documentation technique, namely collecting written material in the form of data obtained from the Finance Department of the Department of Youth, Sports, Culture and Tourism Kapuas Year 2015 and 2016. Data analysis technique use qualitative analysis technique.The results showed that: (1) the Kapuas District Youth, Sports, Culture and Tourism Office had financial management procedures as a guideline governing the financial management process that covered all financial aspects managed by the Kapuas District Culture, Youth and Sports Service. (2) In the financial management procedure owned by the Department of Youth, Sports, Culture and Tourism of the Kapuas Regency, it has complied with government regulations stipulated in the Minister of Home Affairs Regulation Number 13 of 2006.